Green Human Resource Management: Trends in Sustainable and Agile Human Resources Research in SMEs - Muklesh Kumar Tiwari; Neema Gupta (International Journal of Environmental Noise and Pollution Control, 2024)
Small and medium-sized enterprises (SMEs) collectively have a significant environmental impact, despite each individual SME having a relatively small footprint. To mitigate this impact, the implementation of green human resource management practices is crucial for effective workforce management within SMEs. However, SMEs face challenges in executing these strategies and ensuring long-term business continuity. This study aims to establish a theoretical framework for a business model that can assist SMEs in adapting to changing circumstances, addressing sustainability goals and industry shortcomings, and building a resilient and flexible business ecosystem. To address the research problem, the R-based Bibliometrix program was employed. The study followed a five-step process, selecting and analyzing 368 papers from the Scopus database. The findings were visualized using bibliometric tools such as Biblioshiny, VOSviewer, and R Studio. The study's outcomes highlight several crucial variables that form the foundation of the proposed model. The development of the new business model involves identifying key green skills, including both inherent and acquired abilities, and promoting green motivation. The integration of these elements facilitates the adoption of green human resource management practices by SMEs and contributes to the achievement of green organizational citizenship behavior. This behavior is essential for SMEs to effectively implement green HRM approaches. Ultimately, these elements are guided by the principles of environmental management, which drive organizations to enhance their environmental performance and outcomes.
Keywords: HRM; SMEs; Sustainability; environmental performance; green human resource management